Synthesis of Antibacterial Activity of Pyrimidine-2-Thiones and Acetylpyrimidine-2-Thiols - PATEL, P.V.; DESAI, K.R. (Asian Journal of Chemistry, 2010)
Pyrimidie-2-thiones were prepared by heating chalcones with thiourea in ethanolic petassium hydroxide. 1-Acetylpyrimidine-2-thiol derivatives were prepared by the reaction of pyrimidine-2-thiones with acetyl chloride. The structures of the compounds have been confirmed by elemental analysis and spectral analysis. The antibacterial activity of the compounds have also been screened.